Microsatellite sequencing reveals cryptic landscape patterns in European hedgehogs - Loudová, Miroslava; Eliášová, Kristýna; Curto, Manuel; Baránková, Lucie; Meimberg, Harald; Hulva, Pavel; Bolfíková, Barbora Černá (Journal of Vertebrate Biology, 2025)
Understanding genetic population structure and the factors influencing it is fundamental to evolutionary biology and conservation. Hedgehogs in the Western Palearctic provide a model for studying these processes, as their distribution has been shaped by Pleistocene climatic oscillations and recent anthropogenic changes. Secondary contact zones between European (Erinaceus europaeus) and Northern white-breasted (E. roumanicus) hedgehogs have been extensively investigated using a range of analytical methodologies. This study expands upon previous research in the Central European contact zone by incorporating a broader geographic range, increased sample size, and applying short sequence repeat genotyping by amplicon sequencing. Our results reveal a fine-scale population structure previously undetected with microsatellites and genome-wide SNPs. This is a consequence of the higher number of loci and greater universality of sequencing data compared to reading allele lengths using electrophoresis, facilitating international collaborations and enabling greater geographic coverage. We identify a distinct northern and southern cluster within the European hedgehogs and an additional substructure within Northern white-breasted hedgehogs, reflecting the influence of natural and anthropogenic barriers on gene flow. These findings emphasise the role of historical processes and landscape modifications in shaping genetic structure and provide valuable insights into evolutionary dynamics at secondary contact zones.